2016
DOI: 10.1371/journal.pcbi.1004667
|View full text |Cite
|
Sign up to set email alerts
|

Non-monotonic Temporal-Weighting Indicates a Dynamically Modulated Evidence-Integration Mechanism

Abstract: Perceptual decisions are thought to be mediated by a mechanism of sequential sampling and integration of noisy evidence whose temporal weighting profile affects the decision quality. To examine temporal weighting, participants were presented with two brightness-fluctuating disks for 1, 2 or 3 seconds and were requested to choose the overall brighter disk at the end of each trial. By employing a signal-perturbation method, which deploys across trials a set of systematically controlled temporal dispersions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 63 publications
5
43
0
Order By: Relevance
“…Just as past work has taken such early weighting as a signature of bounded accumulation, late weighting has been posited to reflect leaky integration. However, such models have been increasingly updated to accommodate either sort of behavioral signature (Usher and McClelland, 2001; Tsetsos et al, 2012; Bronfman et al, 2016). Thus, while time varying weighting has been identified before, it is almost always discussed as diagnostic about the structure of a decision-making mechanism, i.e., perfect or leaky integration to a bound (fixed or collapsing).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Just as past work has taken such early weighting as a signature of bounded accumulation, late weighting has been posited to reflect leaky integration. However, such models have been increasingly updated to accommodate either sort of behavioral signature (Usher and McClelland, 2001; Tsetsos et al, 2012; Bronfman et al, 2016). Thus, while time varying weighting has been identified before, it is almost always discussed as diagnostic about the structure of a decision-making mechanism, i.e., perfect or leaky integration to a bound (fixed or collapsing).…”
Section: Discussionmentioning
confidence: 99%
“…This notion is supported by experiments in which weighting changes systematically with variable trial length and signal timings (Ghose 2006; Tsetsos et al, 2012; Ossmy et al, 2013; Bronfman et al, 2016), as well as by studies that explore effects of congruency between serially presented samples (Cheadle et al, 2014). Irrespective of a stipulated model or mechanism, these studies point to similar conclusions: subjects may reweigh stimulus information as dictated by the reliability of the evidence and demands of the task.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In particular, it has been argued that primacy in pulsedbased tasks is due to either reaching an accumulator bound (Kiani et al, 2008) or to competition between leaky integrators that mutually inhibit each other (Tsetsos et al, 2012) . Interestingly, it has been recently shown that in humans the degree of primacy and even the monotonicity of the evidence weighting curve can change with stimulus duration, which prompted the authors to postulate a dynamic evidence accumulation mechanism (Bronfman et al, 2016) . Thus, it is conceivable that different decisionmaking and integration mechanisms might be at play depending on stimulus and task features (Piet et al, 2017; Uchida et al, 2006 .…”
Section: Discussionmentioning
confidence: 99%
“…In the perceptual choice tasks commonly used in the laboratory (but see [3][4][5]), performance is maximized by weighing evidence equally across time [1]. Yet, the evidence weighting applied by human and non-human decision-makers often deviates substantially from such flat weighting profiles (but see [6,7]): some studies found stronger weighting of early evidence ('primacy'; [8][9][10][11]), others stronger weighting of late evidence ('recency'; [12][13][14]), and yet others even non-monotonic weighting profiles [15].…”
Section: Introductionmentioning
confidence: 99%